HOW CAN WOMEN'S LEADERSHIP BE EMPOWERED THROUGH RELIGIOUS AND CULTURAL KNOWLEDGE IN BALI? - Sunia Dewi, Putu Ayu; Kerthayasa Suyasa , Tjokorda Maya; Abadi, Mansurni; Nur Pratiwi, Nia (The Ministry of Religious Affairs, The Republic of Indonesia, 2024)
This research explores the intersection of religious, cultural, and educational leadership in Bali, critiquing patriarchal practices and promoting leadership grounded in Balinese local wisdom. Bali, with its deep-rooted traditions, often reinforces patriarchal norms that limit the roles and rights of women in religious and social spheres. Balinese women, while central to community life, often face marginalization. This study investigates how Balinese religious texts, particularly lontar (Palm-leaf manuscript) such as Geguritan Niti Rajasesana and Geguritan Dharma Sesana which contain crucial leadership principles, including catur pariksa and brata nembelas that emphasizing self-awareness, integrity, and religious character that can empower women become leader. This qualitative research uses data analysis techniques: data reduction, data presentation, and data verification. Both manuscript does not directly discuss about the concept of leadership and dismantle patriarchy but is relevantly integrated into praxis progressive women's empowerment based on a more inclusive interpretation of customs and openness to the potential of Balinese women to become leaders based on The five loyalties Hinduism that consist of Loyalty to conscience (Padma Hardhaya), Loyalty to conscience (Satya Wacana), Loyalty to promises (Satya Semaya), Loyalty to people (Satya Mitra), and loyalty to responsibility/trust (Satya Laksana).